Analytical study of drift velocity in low dimensional devices - Ahmadi, Mohammad Taghi; Saad, Ismail; Riyadi, Munawar Agus; Ismail, Razali; Arora, Vijay K. (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
Understanding of quantum limit in low dimensional devices helps to develop the new device types same as Carbon Nanotube Field Effect Transistor (CNTFET) and Naonowire. For each dimensionality the limitations on carrier drift velocity due to the high-field streaming of otherwise randomly velocity vector in equilibrium is reported. The results are based on the asymmetrical distribution function that converts randomness in zero-field to streamlined one in a very high electric field. The ultimate drift velocity for all dimensions is found to be appropriate thermal velocity for a nondegenerately doped sample of silicon, increasing with the temperature, but independent of carrier concentration. However, the ultimate drift velocity is the Fermi velocity for degenerately doped silicon increasing with carrier concentration but independent of the temperature